Simple Thalidomide Analogs in Melanoma: Synthesis and Biological Activity - Alexia Barbarossa; Alessia Catalano; Jessica Ceramella; Alessia Carocci; Domenico Iacopetta; Camillo Rosano; Carlo Franchini; Maria Stefania Sinicropi (Applied Sciences, 2021)
Thalidomide is an old well-known drug that is still of clinical interest, despite its teratogenic activities, due to its antiangiogenic and immunomodulatory properties. Therefore, efforts to design safer and effective thalidomide analogs are continually ongoing. Research studies on thalidomide analogs have revealed that the phthalimide ring system is an essential pharmacophoric fragment; thus, many phthalimidic compounds have been synthesized and evaluated as anticancer drug candidates. In this study, a panel of selected in vitro assays, performed on a small series of phthalimide derivatives, allowed us to characterize compound 2k as a good anticancer agent, acting on A2058 melanoma cell line, which causes cell death by apoptosis due to its capability to inhibit tubulin polymerization. The obtained data were confirmed by in silico assays. No cytotoxic effects on normal cells have been detected for this compound that proves to be a valid candidate for further investigations to achieve new insights on possible mechanism of action of this class of compounds as anticancer drugs.